Implementasi Peraturan Bupati Nomor 33 Tahun 2016 Tentan Pemberian Tambahan Penghasilan Aparatur Sipil Negara Terhadap Peningkatan Disiplin Dan Kinerja Pegawai Pada Kantor Kelurahan Maluhu Kecamatan Tenggarong - Dendi Dwi Safutra; Syahruddin Syahruddin S; Muhammad Hermanto (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract:The purpose of this study was to determine the magnitude of the effect of giving additional employee income (TPP) to increase the level of discipline and employee performance at the Maluhu Sub-District Office in Tenggarong District.The problem is that there are quite a lot of employees who are diligent in being absent in the morning but one hour after that the employee can go straight out of the office and come back one hour later before being absent home in the afternoon. As for discipline in terms of the effectiveness of the use of work time which should not have experienced a significant increase or change. Employees of the Maluhu Urban Village Office are absent only to pursue or fulfill incentive payment requirements.This research was conducted using quantitative methods. The sample used was 24 people. The analysis tool uses 2 linear dependent paradigm regression, with hypothesis testing using the t test and correlation.The results of TPP t count with work discipline is 6.485 while t table with degrees of freedom at the level of 5% (a = 0.05), amounting to 1.717 which means (t count 6.485> t table 1.717). Thus H0 is rejected and H1 is accepted. Thus the first hypothesis proposed in this study was accepted because it proved the truth.The results of TPP t count with employee performance is 4.012 while t table with degrees of freedom at the level of 5% (a = 0.05), amounting to 1.717 which means (t count 4.012> t table 1.717). Thus H0 is rejected and H1 is accepted. Thus the second hypothesis proposed in this study was accepted because it proved the truth.From the results of the comparison of the second partial correlation of the Y variable above, it can be seen that the correlation value between the variables of TPP money and work discipline is more than the value of TPP money with a performance of 0.810 versus 0.650. So that it can be concluded that giving TPP money so far to employees of the Maluhu Village Office in Tenggarong is far more able to have a dominant influence on work discipline than on performance improvement. So that the third hypothesis in this study is accepted. Keywords: Additional Employee Income (TPP), Discipline And Employee Performance